PERANCANGAN KOMUNIKASI VISUAL SEBAGAI MEDIA PROMOSI ALBUM KEDUA BAND BLASPHEMY DOOM BLACK METAL â€œLELEMBUTâ€ - Sandi Kisworo (Canthing, 2012)
Â Â Visual Communication Design of Media Campaign For Second Album Band Black Metal Doom Blasphemy "lelembut", Final Visual Communication Design Academy of Art and Design Indonesia Surakarta.At this final duty the writer makes a visual design of a media campaign konunikasi band's second album Doom Black Metal Blasphemy "lelembut". Preparation of this thesis discusses the band's second album promotional media Doom Black Metal Blasphemy "lelembut".The final task is structured as one of the requirements dalamm achieve expert Associate degree in Visual Communication Design Studies Programme, Academy of Art and Design Indonesia Surakarta. Media is divided into two, namely the media above the line and below the line. With the design is expected to increase public awareness of the existence of underground music community that are interested in buying the album Blasphemy Doom band. Black Metal "lelembut".